(Un)normalizing education : addressing homophobia in higher education and K-12 schools - Jones, Joseph R., 1975- (Emerald Publishing Limited : Information Age Publishing, 2014)
Recently, with the number of students from higher education and K-12 settings committing suicide, it is apparent that homophobia and homophobic bullying are tremendous problems in our schools and universities. However, educators are unclear about an appropriate process for addressing these challenges. In this book, Jones postulates that we must begin exploring the culture of educational environments as they relate to sexual difference, in order to begin conceptualizing ways in which we may begin to address homophobia and heteronormativity. To that end, this book addresses how educators (at all levels) must begin examining how their concepts about different sexual identities are "normalized" through socializing processes and schooling. In doing so, this book examines how individuals construct meanings about homophobia and hate language through "contextual oppositions, " how educational environments maintain a ''false tolerance" when claiming to be tolerant of different sexual identities, how a hierarchy of hate language exists in educational environments, among other issues related to creating safe places for all students. In essence, the book attempts to "un"normalize society's constructions of sexual identity by deconstructing the social norms.
Keywords: Homophobia in high schools -- Prevention.; Homophobia in higher education -- Prevention.; Education -- Schools -- Levels -- Higher.; Counselling and care of students.; Higher education, tertiary education.; elektronické knihy; electronic books